2021
DOI: 10.1111/geb.13311
|View full text |Cite
|
Sign up to set email alerts
|

Human food use increases plant geographical ranges in the Sonoran Desert

Abstract: Aim Climate is usually regarded as the main determinant of plant species distributions. However, past human use of species for food might also have influenced distributions. We hypothesized that human‐mediated dispersal has resulted in food plants occupying more of their potential geographical range. We also hypothesized that key ecological traits could predispose a species to occupy more of its potential climatic geographical range and be selected by humans for food. Location The Sonoran Desert of south‐weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Both wild harvesting and deliberate propagation of plants for food significantly increase plants' distribution (Flower et al, 2021). We also found that cultivated species occupied significantly different environmental niches than a non-cultivated comparator.…”
Section: The Environmental Niche Range Sizes and Traits Of Cultivated...mentioning
confidence: 68%
See 4 more Smart Citations
“…Both wild harvesting and deliberate propagation of plants for food significantly increase plants' distribution (Flower et al, 2021). We also found that cultivated species occupied significantly different environmental niches than a non-cultivated comparator.…”
Section: The Environmental Niche Range Sizes and Traits Of Cultivated...mentioning
confidence: 68%
“…The range sizes of these two species are almost 10 times larger than the median of the range sizes of non‐cultivated tree species. This relationship may well be reciprocal; the species selected for widespread cultivation are likely able to thrive in a variety of conditions as well as being useful (i.e., Z. mauritiana ; a tree found abundantly in arid/semi‐arid places; Singh et al, 2021; Singh & Meghwal, 2020; and also in humid forests; eFloras, 2008) and species used by humans fill more of their potential ranges than unused species (Flower et al, 2021). Flower et al (2021) found that unused plant species filled significantly less of their range compared to species used for food, but that the difference was less clear when comparing food plants with species used for other purposes (i.e., medicinally).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations